Carnitine Traffic in Cells. Link With Cancer - Console, Lara; Scalise, Mariafrancesca; Mazza, Tiziano; Pochini, Lorena; Galluccio, Michele; Giangregorio, Nicola; Tonazzi, Annamaria; Indiveri, Cesare (Frontiers in Cell and Developmental Biology, 2020)
Metabolic flexibility is a peculiar hallmark of cancer cells. A growing number of observations reveal that tumours can utilize a wide range of substrates to sustain cell survival and proliferation. The diversity of carbon sources is indicative of metabolic heterogeneity not only across different types of cancer but also within those sharing a common origin. Apart from the well-assessed alteration in glucose and amino acid metabolisms, there are pieces of evidence that cancer cells display alterations of lipid metabolism as well; indeed, some tumours use Fatty Acid Oxidation (FAO) as the main source of energy and express high levels of FAO enzymes. In this metabolic pathway, the cofactor carnitine is crucial since it serves as a "shuttle-molecule" to allow fatty acid acyl moieties entering the mitochondrial matrix where these molecules are oxidized via the β-oxidation pathway. This role, together with others played by carnitine in cell metabolism, underlies the fine regulation of carnitine traffic among different tissues and, within a cell, among different subcellular compartments. Specific membrane transporters mediate carnitine and carnitine derivatives flux across the cell membranes. Among the SLCs, the plasma membrane transporters OCTN2 (SLC22A5), CT2 (SLC22A16), MCT9 (SLC16A9) and ATB0,+ (SLC6A14) together with the mitochondrial membrane transporter CAC (SLC25A20) are the most acknowledged to mediate the flux of carnitine. The concerted action of these proteins creates a carnitine network that becomes relevant in the context of cancer metabolic rewiring. Therefore, molecular mechanisms underlying modulation of function and expression of carnitine transporters are dealt with furnishing some perspective for cancer treatment.